Vocational education reform across the Taiwan Strait: A comparative analysis of governance scale and institutional ecology - Xiangjie Zheng; Kun Liu; Yuheng Yao; Kangzhao Cai (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2026)
This study compares vocational education reform in Taiwan and Mainland China to explain why similar reform goals are translated into different institutional practices. Previous cross-strait studies have often examined the two systems separately or compared individual policy measures, while paying limited attention to the institutional logic linking governance scale, institutional ecology, and industrial transition pathways. Using qualitative empirical document analysis within a comparative case-study design, the study analysed 35 core policy, legal, statistical, institutional, and academic sources. Documentary evidence was coded using an integrated covering governance structure, system scale and institutional composition, curriculum and major adjustment, industry–education cooperation, teacher development, and digital transformation. The findings reveal convergence in the shared emphasis on applied talent cultivation, practical learning, and stronger industry linkages, but divergence in the institutional mechanisms through which these objectives are implemented. Taiwan’s relatively smaller and more diversified technical and vocational education system promotes flexible learning pathways, private institutional participation, and industry–academia collaboration, whereas Mainland China’s large-scale system emphasizes national coordination, strategic programme restructuring, school–enterprise cooperation, and workforce development aligned with industrial upgrading. The study contributes an integrated six-dimensional comparative framework for analysing vocational education reform in culturally connected yet institutionally distinct contexts and provides practical insights for context-sensitive policy learning and vocational education reform.